KORELASI INDEKS MASSA TUBUH DENGAN DERAJAT KEPARAHAN SERANGAN MIGREN TANPA AURA - Andry Andry; Muhammad Akbar; Hasmawati Basir (NEURONA, 2019)
THE CORRELATION BETWEEN THE BODY MASS INDEX AND THE SEVERITY OF MIGRAINE ATTACK WITHOUT AURAABSTRACTIntroduction: In Indonesia, there has been only a few studies that correlate Body Mass Index (BMI) to severity of migraine.Aim: To identify the correlation between the body mass index and the severity of migraine attack  without aura.Methods:  The research used the cross sectional design method. The subjects’ age was 18 years or above, and they were treated at the neurology outpatient clinic of Dr. Wahidin Sudirohusodo Hospital and its networking hospitals from June through September 2018. The measurement of Body Mass Index (BMI) of the subjects was conducted, and the level of migraine severity was determined using the numeric pain rating scale (NPRS), while the frequency of migraine attacks was determined in 1 month during the last 3 months  of the study.Results: The research results revealed that 45 samples met the inclusion criteria, consisting of 86.7% women and 13.3% men. By using Spearman’s test, it was found that there was a correlation between the BMI and the pain intensity, and between the BMI and the frequency of the migraine attacks.Discussion: There were correlations between BMI and pain intensity which confounded by sleep disorder and mi- graine prophylaxis, and between BMI and the frequency of migraine attacks which confounded by prophylaxis of migraine without aura.Keywords: BMI, migraine rant, obesity, severityABSTRAK Pendahuluan: Penelitian yang menghubungkan indeks massa tubuh (IMT) dengan derajat keparahan migren masih sedikit di Indonesia.Tujuan: Mengetahui hubungan IMT dengan derajat keparahan serangan migren tanpa aura.Metode: Penelitian ini menggunakan metode potong lintang. Subjek berumur 18 tahun atau lebih dan berobat ke Poliklinik Neurologi RSUP Dr. Wahidin Sudirohusodo dan rumah sakit jejaring antara Juni hingga September 2018. Terhadap subjek dilakukan pengukuran IMT. Derajat keparahan migren ditentukan secara kuantitatif melalui penggunaan numeric pain rating scale (NPRS) dan ditentukan frekuensi serangan migren dalam satu bulan pada interval tiga bulan terakhir saat dilakukan penelitian.Hasil: Didapatkan 45 sampel yang memenuhi kriteria inklusi yang terdiri dari 86,7% perempuan dan 13,3% laki-la- ki. Dengan menggunakan uji Spearman, didapatkan korelasi antara IMT dan tingkat nyeri dan frekuensi serangan migren.Diskusi: Terdapat korelasi antara IMT, dengan tingkat nyeri yang dirancu dengan gangguan tidur, dan pengobatan preventif, dan antara IMT dengan frekuensi serangan yang dirancu dengan pengobatan preventif  pada penderita migren tanpa aura.Kata kunci: Derajat keparahan, IMT, migren, obesitas